2015
DOI: 10.1038/srep11716
|View full text |Cite
|
Sign up to set email alerts
|

Detection and mapping of illicit drugs and their metabolites in fingermarks by MALDI MS and compatibility with forensic techniques

Abstract: Despite the proven capabilities of Matrix Assisted Laser Desorption Ionisation Mass Spectrometry (MALDI MS) in laboratory settings, research is still needed to integrate this technique into current forensic fingerprinting practice. Optimised protocols enabling the compatible application of MALDI to developed fingermarks will allow additional intelligence to be gathered around a suspect’s lifestyle and activities prior to the deposition of their fingermarks while committing a crime. The detection and mapping of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
96
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 25 publications
0
96
0
Order By: Relevance
“…Fingermarks spiked with dimethylbenzylammonium ion (DMA) were prepared using a contacttransfer methodology as previously reported 4 ; briefly, a total of 100 µL of a 10 µg/mL MeOH solution of the compound was deposited onto glass slides. The solvent was allowed to evaporate and either a natural or ungroomed fingertip was rubbed across the entirety of the surface in order to ensure equal distribution of the exogenous species on the fingertip, before depositing a fingermark onto an aluminium slide.…”
Section: Latent Fingermark Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fingermarks spiked with dimethylbenzylammonium ion (DMA) were prepared using a contacttransfer methodology as previously reported 4 ; briefly, a total of 100 µL of a 10 µg/mL MeOH solution of the compound was deposited onto glass slides. The solvent was allowed to evaporate and either a natural or ungroomed fingertip was rubbed across the entirety of the surface in order to ensure equal distribution of the exogenous species on the fingertip, before depositing a fingermark onto an aluminium slide.…”
Section: Latent Fingermark Depositionmentioning
confidence: 99%
“…As a result, protocols were developed to make MALDI-MS based methods compatible with the prior application of many fingermark enhancement techniques (FET) [2][3][4] . These methods have been directly trialled on crime scene evidence (stains and marks) in collaboration with WYP and some of the results have been published in peer-reviewed journals 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The field of fingerprint chemical analysis is also a rapidly growing research area, starting from a recent paradigm shift in the forensic community for using fingerprints for more than just their ridge detail [21][22][23][24][25][26][27][28][29]. It has been previously shown that the chemical composition relates to the age of a latent fingerprint [28], the sex of the donor [24], their drug habits or medical history [17][18][19][20], the way they interact with development reagents [21] and might even be used to confirm their identity using their amino acid profile [29] or to verify their location on questioned documents [23]. This may be useful when a fingerprint is smudged or details of the donor are not contained within the fingerprint database.…”
Section: Introductionmentioning
confidence: 99%
“…This may be useful when a fingerprint is smudged or details of the donor are not contained within the fingerprint database. Many techniques have been proposed for these applications, including spectroscopic techniques [30], which lack the selectivity of mass spectrometry methods; chromatography based approaches [22,29] which require considerable sample preparation and consume at least an entire fingerprint; and vacuum based methods [20][21][22][23][24][25], which have lower sample throughput and have been shown to degrade fingerprint chemistry [31].…”
Section: Introductionmentioning
confidence: 99%
“…According to Veselago's theory, molecules with SRRs configurations such as extended metal atom chains (EMACs), have led a fresh direction of physical and chemical research. Recently many fabulous works in different fields come forth, such as invisible cloaking, [38][39][40][41][42][43] liquid crystal magnetic control, 44 anapole moment, 45 detection of latent fingermarks, [46][47][48] etc. Inspired by these ideas, negative refraction plays more and more important role in forensic science field since it is a non-damaged optical method to test materials.…”
mentioning
confidence: 99%